2019
DOI: 10.4103/ijoy.ijoy_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of yoga and mindfulness in severe mental illnesses: A narrative review

Abstract: Background:Yoga has its origin from the ancient times. It is an integration of mind, body, and soul. Besides, mindfulness emphasizes focused awareness and accepting the internal experiences without being judgemental. These techniques offer a trending new dimension of treatment in various psychiatric disorders.Aims:We aimed to review the studies on the efficacy of yoga and mindfulness as a treatment modality in severe mental illnesses (SMIs). SMI includes schizophrenia, major depressive disorder (MDD), and bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Several works have studied the role of yoga in the overall health and a healthy lifestyle [15], [4], [5]. Also, yoga has been proposed in severe mental illnesses: it was found a reduction in general psychopathology ratings and an improvement in cognition and functioning in schizophrenic patients, and a significant benefit in reducing the severity of depressive symptoms [16]. In those studies which focus on the autonomic function, they found an increase in parasympathetic activity, a decrease in sympathetic activity and an overall increase heart rate variability [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several works have studied the role of yoga in the overall health and a healthy lifestyle [15], [4], [5]. Also, yoga has been proposed in severe mental illnesses: it was found a reduction in general psychopathology ratings and an improvement in cognition and functioning in schizophrenic patients, and a significant benefit in reducing the severity of depressive symptoms [16]. In those studies which focus on the autonomic function, they found an increase in parasympathetic activity, a decrease in sympathetic activity and an overall increase heart rate variability [4].…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent review of yoga and mindfulness in severe mental illness found reasonable evidence for symptom reduction in psychosis and depression, although evidence is sparse for bipolar disorder. 3 Two recent studies reported successful treatment of major depression using yoga as the only treatment (details of these and the other trials mentioned in this editorial are available from the author on request). An 8-week RCT of a hatha yoga intervention as monotherapy for mild-to-moderate major depression compared with attention-control education sessions found that the yoga participants ( n = 20) had significantly greater decline in depression scores than the control group ( n = 18) and more of them achieved remission.…”
Section: Yoga As Therapy For Psychiatric Disordersmentioning
confidence: 99%
“…Care has not been broadly attempted, yet the accessible proof has appeared in improving crazy manifestations, improving dimension of working, and influence guideline. 7 The Laughter Yoga (LY) assemble had factually more noteworthy abatements in gloom and upgrades in psychological wellness related personal satisfaction. 6 The normal routine with regards to Yoga can be considered as a viable intercession in improving physical (diminishes pulse, circulatory strain, blood glucose, oxidative harm, exhaustion, shortcoming, dread of fall, and improve pulse fluctuation, baroreflex affectability, insulin affectability, physical capacities, portability, adaptability, and urinary incontinence), mental (lessens misery, uneasiness), passionate (decreases outrage, stress, pressure and improve self-adequacy), social (improve life fulfilment), and essential (improved imperativeness) planes of old people, offering a superior nature of rest and personal satisfaction.…”
Section: Role Of Yogamentioning
confidence: 99%